Pemberdayaan Masyarakat Nelayan di Desa Pabeanudik: Studi Kasus Perlindungan Hukum - Mulyadi Mulyadi; Kayus K. Lewoleba; Yuliana Yuli Wahyuningsih; Satino Satino; Dwi Aryanti Ramadhani (SIGn Jurnal Hukum, 2022)
This study aims to examine the implementation of legal protection for the fishermen community in Pabeanudik Village. This research combines normative juridical and empirical research methods. The primary data were collected using direct interviews, while the secondary data was collected using literature study techniques. The data obtained in this research were then analyzed qualitatively to describe the problem and answer study purposes. The results show that there are contradictory explanations from several laws and regulations regarding the status of fishermen as legal subjects. In addition, most Fishers do not receive guarantees of safety and security from Fishing Vessel Owner when going to sea on the high seas. In addition to weak legal protection, Fishers also received less guidance and guarantees for legal assistance from the Local Government. Therefore, it is recommended that the Government make amendments to several laws and regulations. In this case, to equalize the explanation of the status of fishermen as legal subjects. Furthermore, the Local Government must implement protection and empowerment policies regulated in laws and regulations. These include business certainty, elimination of high-cost economic practices, provision of production facilities and infrastructure, guarantees against risks in the fishing business, and assistance for fishermen who have difficulty catching fish. In addition, support in the form of protection and empowerment is given exclusively to small fishermen and fishers so that the series of problems described can be minimized in the future.